Polymer insulating material for 110kV overhead bare conductor and preparation method thereof
By developing a polymer insulating material containing a variety of high-performance components and using coated robots for rapid curing, the problem of lack of high-voltage resistant insulating material on 110kV overhead bare wires was solved, and efficient insulation and safety improvement were achieved.
Patent Information
- Application Number
- CN202411894300.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art lacks high-voltage and corrosion-resistant insulation materials used on 110kV overhead bare wires, resulting in frequent safety hazards and accidents.
A polymer insulating material was developed, containing hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microbeads, hydrophobic vapor phase white carbon black and other components, and quickly cured at room temperature through a special coating robot.
It has achieved efficient insulation of 110kV overhead bare wires, which improves the material's high pressure resistance, weather resistance, mechanical strength and flame retardant properties, extends its service life, and reduces the risk of accidents.
Smart Images

Figure CN119823577A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating materials, and in particular to a polymer insulating material for 110kV overhead bare conductors and a preparation method thereof. Background Art
[0002] Overhead lines are widely distributed, long, and have complex line environments. Overhead lines have become the main form of power transmission, and their safe and stable operation directly affects the reliability of the power supply system. However, exposed overhead lines are prone to accidents when passing through densely populated areas, woods, fish ponds, etc., causing personal and property losses and injuries.
[0003] In order to solve the problem of frequent accidents such as short circuit, tripping, and electric shock caused by the low height of overhead power lines, at present, for 10kV overhead distribution lines and 35kV and 66kV overhead transmission lines, on-site insulation operations have been carried out nationwide by using live coating robots to coat a layer of insulating material that can be quickly cured at room temperature on the bare conductors. For 110kV overhead transmission lines with relatively high voltage levels, due to their relatively low tower heights, there is also a problem of insufficient crossing distance in actual operation, resulting in major safety hazards. For example, there are some super-high trees that are difficult to cut down under the line, which can easily cause line short-circuit tripping accidents; illegal construction and illegal building in the line protection area also seriously threaten the operation of the line. Therefore, there is also a need for on-site insulation of 110kV overhead transmission lines. In order not to affect the normal operation of transmission lines, the power grid also urgently needs to develop an insulating material that can be quickly cured at room temperature and is suitable for 110kV overhead transmission lines. It can be automatically coated on the overhead bare wires by a matching live working robot to form an insulating protective layer, so as to fundamentally solve the problem of insufficient crossing distance of 110kV overhead transmission lines.
[0004] Therefore, high voltage resistant and corrosion resistant insulating materials used for coating on 110kV overhead bare conductors need to be further developed and improved. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a polymer insulating material for 110kV overhead bare conductors and a preparation method thereof, aiming to solve the problem that the prior art lacks high-voltage and corrosion-resistant insulating materials for coating on 110kV overhead bare conductors.
[0006] The technical solution of the present invention is as follows:
[0007] A polymer insulating material for 110kV overhead bare conductors comprises, by weight: 52-53 parts of hydroxy silicone resin of model FD20, 8-8.5 parts of hydroxy silicone resin of model TH-3051, 12-16 parts of fluorosilicone resin, 48-55 parts of tetrafluoroethylene, 5-10 parts of hollow glass microspheres, 0.5-1 part of magnesium hydroxide, 0.2-0.25 parts of methyltrimethoxysilane, 4.5-5 parts of vinyltrimethoxysilane, 2-5 parts of calcium carbonate, 7-11 parts of hydrophobic fumed white carbon black, 1.5-2.5 parts of platinum catalyst, 1-1.5 parts of aminopropyltriethoxysilane, 0.2-0.25 parts of black paste, and 0.5-1.5 parts of hydroxy silicone resin with a viscosity of 350cs.
[0008] The polymer insulating material for 110kV overhead bare conductors, wherein the hollow glass microspheres are spherical powdered materials with a hollow structure, with hard glass on the outside and filled with inert gas on the inside, with a particle size of 5-100 microns and a density of 0.3-0.8g / ml.
[0009] The polymer insulating material for 110kV overhead bare conductor, wherein the hollow glass microspheres comprise, by mass percentage, 55-65% SiO2, 26-35% Al2O3, 0.2-1% Fe2O3, 0.5-4% Na2O, 0.5-4% K2O, 0.2-0.6% CaO, 1-2% MgO, and 0.5-2% TiO2.
[0010] The polymer insulating material for 110kV overhead bare conductors, wherein the hydrophobic fumed silica in the polymer insulating material accounts for 11-19% of the total mass of the hydroxy silicone resin.
[0011] The polymer insulation material for 110kV overhead bare conductor, wherein the specific surface area of the hydrophobic fumed silica is 150-400m 2 / g, silicon dioxide content ≥99.8%.
[0012] The polymer insulating material for 110 kV overhead bare conductor, wherein the density of the methyltrimethoxysilane is 0.955 g / cm 3 , boiling point is 102-104°C, refractive index is 1.371; density of the vinyl trimethoxysilane is 0.9±0.1g / cm 3 , boiling point is 123℃, and refractive index is 1.3920.
[0013] The polymer insulation material for 110kV overhead bare conductor, wherein the model of the platinum catalyst is CAT-PL-56, and the platinum ion concentration thereof is 50000ppm.
[0014] The polymer insulating material for 110kV overhead bare conductor, wherein the model of the fluorosilicone resin is LS8722, the fluorine content thereof is 40%, and the viscosity is 100000cs.
[0015] A method for preparing a polymer insulating material according to the present invention, comprising the steps of:
[0016] Add FD20 hydroxy silicone resin, FD80 hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microspheres and magnesium hydroxide into a disperser in sequence, stir and disperse them, pass cooling water, evacuate to -0.09 to -0.1 MPa, and continue to disperse for 30-60 minutes to obtain a first mixed material;
[0017] The first mixed material is transferred to a three-roll mill for grinding, and then the first mixed material is transferred to a disperser, methyltrimethoxysilane and vinyltrimethoxysilane are added, cooling water is added for dispersion, and then calcium carbonate and hydrophobic fumed silica are added, dispersed and mixed for 10-30 minutes, and vacuumed to a vacuum degree of -0.09 to -0.1Mpa, maintained for 30-50 minutes, and stirring and dispersing is stopped, and the vacuum is released to obtain a second mixed material;
[0018] Platinum catalyst, aminopropyl triethoxysilane and black slurry were added to the second mixture, and after stirring and dispersing, the viscosity was adjusted by adding hydroxy silicone resin with a viscosity of 350 cs to prepare a polymer insulation material for 110 kV overhead bare conductors.
[0019] The method for preparing the polymer insulating material, wherein the rotation speed of the disperser is 1800-2500 r / min.
[0020] Beneficial effects: The present invention uses hydroxy silicone resin material as the system material for 110kV insulation coating, and then improves the material formula from the aspects of high voltage resistance, light weight, weather resistance, thixotropy, flame retardancy, adhesion, mechanical strength and wear resistance, and finally obtains a polymer insulation material that can be used for 110kV overhead bare conductors. This material is a single-component high-viscosity liquid insulation material that cures at room temperature. By using a special coating robot, this insulation material is coated on the 110kV overhead bare conductor, which can insulate the surface of the bare conductor and can tightly wrap the overhead bare conductor to prevent leakage accidents. The polymer insulation material provided by the present invention has been tested many times, and its AC breakdown voltage can reach 130kV / 6mm. Due to the silicone system, its service life reaches more than 15 years. The polymer insulating material provided by the present invention is cured at room temperature, with a surface curing time of 30 minutes and a complete curing time of 24 hours. After being coated on an overhead bare conductor, it can be powered on and operated without affecting its load-bearing capacity. The polymer insulating material of the present invention has excellent mechanical properties, with a tensile strength of 10.8 MPa and an elongation at break of 680%. After aging for 1008 hours, the change rate of the tensile strength is only -5.18%, and the change rate of the elongation at break is only -12.67, showing better weather resistance and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a flow chart of a method for preparing a polymer insulating material for 110kV overhead bare conductors.
[0022] Figure 2 This is a state diagram of a coating robot coating polymer insulation material on an overhead bare conductor.
[0023] Figure 3 This is a diagram for testing the withstand voltage of wires coated with polymer insulation materials. DETAILED DESCRIPTION
[0024] The present invention provides a polymer insulating material for 110kV overhead bare conductor and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] The invention provides a polymer insulating material for a 110kV overhead bare conductor. The polymer insulating material comprises, by weight, 52-53 parts of a hydroxy silicone resin of model FD20, 8-8.5 parts of a hydroxy silicone resin of model TH-3051, 12-16 parts of a fluorosilicone resin, 48-55 parts of tetrafluoroethylene, 5-10 parts of hollow glass microspheres, 0.5-1 parts of magnesium hydroxide, 0.2-0.25 parts of methyltrimethoxysilane, 4.5-5 parts of vinyltrimethoxysilane, 2-5 parts of calcium carbonate, 7-11 parts of hydrophobic fumed white carbon black, 1.5-2.5 parts of a platinum catalyst, 1-1.5 parts of aminopropyltriethoxysilane, 0.2-0.25 parts of black paste, and 0.5-1.5 parts of a hydroxy silicone resin with a viscosity of 350cs.
[0026] In the present invention, the hydroxy silicone resin of model FD20 and the hydroxy silicone resin of model TH-3051 are both purchased from Wacker International Group Co., Ltd., Germany, and the density of both is 0.98 g / cm 3 , the flash point is 430°C, the viscosity of the hydroxy silicone resin model FD20 is 20000cs, and the viscosity of the hydroxy silicone resin model TH-3051 is 80000cs; hydroxy silicone resin is a silicone resin containing a hydroxyl (-OH) functional group, which has good heat resistance, weather resistance, electrical insulation and low surface tension. FD20 and FD80 have different molecular weights and viscosities. This embodiment uses FD20 and FD80 as the main resin system materials of the polymer insulation material, which can adjust the fluidity and curing speed of the material, and at the same time enhance the overall performance of the material, such as flexibility and hardness.
[0027] Since the strength of hydroxy silicone resin is relatively poor, it can only be used after adding reinforcing fillers. Therefore, the dispersion of fillers in the rubber matrix and the interface bonding strength between fillers and the matrix have a great influence on the performance of rubber. In this embodiment, due to the large specific surface area of white carbon black (150-400m 2 / g), and contains a large number of polar groups Si-OH on the surface. Although the -Si-O-Si-O- main chain has a certain ionicity due to the different electronegativity of the two Si-O atoms, the main chain is polar to the outside because it is shielded by polar groups such as hydroxyl groups. This makes silica very incompatible with non-polar polysiloxane macromolecular chains (silicone resins). Adjacent silica particles can form hydrogen bonds, resulting in serious agglomeration in the rubber matrix and poor dispersion, which in turn affects the reinforcement of silicone rubber. Therefore, the hydrophobic fumed silica used in this embodiment is obtained by treating nano-scale fumed silica with hexamethyldisilazane to shield some hydroxyl groups. The molecular structure of hexamethyldisilazane (HMDS) contains silicon-nitrogen bonds (Si-N) and methyl groups (—CH3), which can react with hydroxyl groups to form silicon-oxygen bonds (Si-O) and release ammonia (NH3). When HMDS comes into contact with nano-scale silica, the silicon-nitrogen bonds in its molecules will chemically react with the hydroxyl groups on the surface of silica. During the reaction, the silicon atoms of HMDS form silicon-oxygen bonds with the hydroxyl oxygen atoms on the surface of silica, and at the same time, the methyl groups on the nitrogen atoms of HMDS are retained and covered on the surface of silica. This reaction process effectively "shields" part of the hydroxyl groups on the surface of silica, reducing its hydrophilicity. Therefore, after the HMDS treatment, the number of surface hydroxyl groups of the silica is reduced, the hydrophilicity is reduced, and the hydrophobicity is enhanced; at the same time, due to the introduction of methyl groups, the compatibility between the silica and the silicone rubber matrix is improved. As a non-polar group, the methyl group can better interact with the non-polar part in the silicone rubber. The improved silica is more evenly dispersed in the silicone rubber, and the agglomeration phenomenon is reduced. Its better dispersibility and compatibility enable the hydrophobic fumed silica to be more effectively used as a reinforcing filler, thereby improving the mechanical strength of the silicone rubber. The improvement in mechanical strength is manifested in the enhancement of mechanical properties such as tensile strength and tear strength.
[0028] In this embodiment, the addition of hydrophobic fumed silica can play a reinforcing role, but it will reduce its hydrophobic migration to a certain extent. Therefore, a reinforcing filler and a semi-reinforcing filler can be used in combination, that is, 2-5 parts of calcium carbonate and 7-11 parts of hydrophobic fumed silica can make the silicone rubber have better adhesion strength and heat and moisture resistance. In this embodiment, the specific surface area of the hydrophobic fumed silica is preferably 150-400m 2 / g, silicon dioxide content ≥99.8%.
[0029] As mentioned above, adding silica to silicone rubber can significantly improve the mechanical properties of rubber, such as tensile strength and tear strength. However, the addition of silica will reduce the hydrophobic migration of silicone rubber, which will affect the performance of silicone rubber in some applications. Calcium carbonate is a common inorganic filler with good thermal and chemical stability. Adding CaCO3 to silicone rubber can improve the heat resistance and moisture resistance of rubber, because CaCO3 itself is not easily decomposed by heat and is not easy to absorb water. When silica and CaCO3 are used together, the two can produce a synergistic effect. Silica mainly provides a reinforcement effect to enhance the mechanical properties of silicone rubber, while CaCO3 improves the heat and moisture resistance of silicone rubber through its thermal and chemical stability. In addition, the addition of CaCO3 can also balance the problem of reduced hydrophobic migration caused by silica to a certain extent, because CaCO3 itself has good hydrophilicity and can improve the compatibility of silicone rubber with water.
[0030] In this embodiment, since fluorine atoms have a strong ability to bind electrons, it is difficult for electrons to escape from molecules, which can greatly improve the insulation performance of the material. Therefore, this embodiment improves the insulation performance of silicone rubber by adding fluorine-containing substances (such as fluorosilicone rubber, fluorocarbon resin, and fluorine-based plastics). The present application also found that introducing F elements into the coating can also make the coating have high weather resistance, high adhesion, and excellent hydrophobicity (static contact angle exceeds 120°). In this embodiment, 12-16 parts of fluorosilicone resin and 48-55 parts of tetrafluoroethylene are added to the polymer insulating material, wherein the fluorosilicone resin combines the chemical corrosion resistance of fluorine compounds and the high and low temperature resistance of silicone resin, which improves the weather resistance, chemical corrosion resistance and electrical insulation of the polymer insulating material. It can also increase the hydrophobicity of the material surface and reduce moisture absorption. In this embodiment, the preferred model of the fluorosilicone resin is LS8722, with a fluorine content of 40% and a viscosity of 100000cs; tetrafluoroethylene is a fluorine-containing monomer, which is commonly used in the preparation of fluoropolymers, such as polytetrafluoroethylene (PTFE). Here, it may act as a cross-linking agent or comonomer and react with silicone resin, etc., thereby improving the chemical resistance, high temperature resistance and electrical insulation performance of the material.
[0031] This embodiment also adds 5-10 parts of hollow glass microspheres (HGM) to the polymer insulating material. Hollow glass microspheres (HGM) are a new type of spherical powder material with a hollow structure. The outside is hard glass and the inside is filled with inert gas. Its particle size is 5-100 microns and its density is 0.3-0.8g / ml. Since HGM has a series of advantages such as low density, low thermal conductivity, high specific strength, good fluidity, decomposition temperature and mechanical damping, this embodiment reduces the density of the polymer insulating material and improves its mechanical properties by adding lightweight hollow glass microsphere fillers. The hollow glass microspheres include, by mass percentage: 55-65% SiO2, 26-35% Al2O3, 0.2-1% Fe2O3, 0.5-4% Na2O, 0.5-4% K2O, 0.2-0.6% CaO, 1-2% MgO, and 0.5-2% TiO2. Compared with other inorganic materials, the special feature of HGM is that it is spherical with a smoother outline and has better filling fluidity. Even if a large amount of HGM is added to the matrix, it has little effect on the processability and viscosity of the composite system. At the same time, it can reduce the shrinkage rate of HGM-filled polymer products, and unlike other angular fillers, it will not become a stress concentration point and reduce the mechanical properties of the composite material.
[0032] In the polymer insulating material of this embodiment, 0.2-0.25 parts of methyltrimethoxysilane and 4.5-5 parts of vinyltrimethoxysilane are also added. Both silanes are crosslinking agents, which are used to form a network structure during the curing process to improve the strength, heat resistance and chemical resistance of the material. Among them, methyltrimethoxysilane may provide more methyl groups to enhance hydrophobicity; vinyltrimethoxysilane participates in the reaction through the vinyl group to increase the crosslinking density. The quality of the coating adhesion mainly depends on the degree of wettability of the film-forming substance to the substrate and the polar groups. When the silicone rubber coating is sprayed on the surface of the bare wire, a large amount of -OH in the silicone rubber will undergo a condensation reaction with the hydroxyl group on the surface of the attachment, so that the colloid itself is tightly combined with the attachment, and the coupling agent undergoes a condensation reaction with the residual bonds of the silicone resin macromolecule and the hydroxyl group on the surface of the bare wire, which is equivalent to having a longer macromolecular chain tightly attached to the surface of the object, greatly improving the adhesion. When the mixture of vinyl trimethoxysilane and methyl trimethoxysilane in this embodiment is used as a crosslinking agent, the adhesion of the obtained polymer insulating material can be as high as level 1 or above; in this embodiment, the density of the methyl trimethoxysilane is 0.955 g / cm 3 , boiling point is 102-104°C, refractive index is 1.371; density of vinyl trimethoxy silane is 0.9±0.1g / cm 3 , boiling point is 123℃, and refractive index is 1.3920.
[0033] In the polymer insulating material of this embodiment, 1-1.5 parts of aminopropyltriethoxysilane are also added. The aminopropyltriethoxysilane is a coupling agent, which is mainly used to improve the interface bonding force between inorganic fillers (such as white carbon black) and organic resins, and improve the overall performance and stability of the material.
[0034] In the polymer insulating material of this embodiment, 1.5-2.5 parts of platinum catalyst are also added, which is more environmentally friendly than toxic organic tin catalysts. The platinum catalyst is used to accelerate the cross-linking reaction of silicone resin and reduce the curing temperature and time. It is essential to achieve a fast and efficient curing process and ensure that the material has excellent performance after curing. In this embodiment, the preferred model of the platinum catalyst is CAT-PL-56, and its platinum ion concentration is 50000ppm.
[0035] The polymer insulating material provided in this embodiment needs to have good thixotropy, so that it can be shaped when coated on the bare wire and keep its coating uniformly attached to the bare wire without being affected by gravity. In this embodiment, the consistency of the material is adjusted to below 8.0 by adjusting the process, so that the thixotropic shaping property of the material can be achieved; at the same time, calcium carbonate and magnesium hydroxide are added as thixotropic materials, which can effectively improve the good thixotropy of the organic silicon insulating material.
[0036] The 0.5-1 part of magnesium hydroxide and 1.5-2.5 parts of platinum catalyst added to the polymer insulating material of this embodiment can also be used as flame retardants. Specifically, the combustion process of polymers is generally divided into two stages. The first stage is the decomposition process of the polymer, and the second stage is the combustion process of the decomposition product. The mechanism of silicone rubber combustion is that the low molar mass cyclic polysiloxane generated by cracking burns in the presence of ambient oxygen, and the residue after combustion is SiO2 and other inorganic fillers. Therefore, improving the flame retardancy of silicone rubber should be considered from the aspects of increasing its thermal decomposition temperature, increasing the combustion residue, and slowing down the rate of generation of combustible gas. In this embodiment, adding a certain amount of platinum catalyst can make the silicone rubber have excellent flame retardant and flame extinguishing properties. Its flame retardant effect mainly has two kinds: one is to prevent the formation of transition complexes that promote depolymerization; the other is that during cracking, it is beneficial to fix a part of the condensation product through the intermediate of the filler or oxide to form an insulating barrier layer; magnesium hydroxide is a filler with a large specific heat capacity. Its heat storage and thermal conductivity prevent the material from reaching the decomposition temperature or absorb heat through the thermal decomposition of the flame retardant, thereby slowing down or stopping the temperature rise and achieving a flame retardant effect; and the decomposition temperature of the magnesium hydroxide is different from that of Al(OH)3 (>300℃), so it is more suitable for polymers with high decomposition temperature, and its oil absorption is far higher than Al(OH)3, up to 40-50g / 100g, so on the basis of being a flame retardant, it will also improve the water-repellent and oil-repellent properties of the coating.
[0037] In some embodiments, the hydrophobic fumed silica in the polymer insulating material accounts for 11-19% of the total mass of the hydroxy silicone resin. This embodiment improves the mechanical strength of the material by adding hydrophobic fumed silica, but the study found that with the increase in the amount of hydrophobic fumed silica added, the mechanical strength of the silicone rubber continues to increase, but after reaching a peak, the mechanical strength decreases. It is analyzed that with the increase in the amount of hydrophobic fumed silica added, the degree of crystallization of the silica aggregate increases, the points of action on the silicone rubber molecular chain increase, the adsorption effect is stronger, and the mechanical strength of the silicone rubber increases accordingly. However, when the amount of silica added is too large, the number of connection points between the silicone rubber molecular chain and the silica increases, the more firmly the molecular chain is fixed around the silica aggregate, the lower the flexibility, and the elasticity of the silicone rubber decreases. At this time, if an external force acts on the silicone rubber, due to the decrease in the activity of the macromolecular chain, the internal stress distribution of the silicone rubber presents an uneven state, so that the molecular chain with too much stress is destroyed first, so the mechanical strength of the material decreases instead. When the material is stretched, the entire cross section of the material is subjected to stress, and the stress distribution is relatively uniform. When the material is torn, the stress distribution is much more uneven than when it is in the stretched state, and the maximum stress value is higher, so the molecular chain is more easily destroyed. This is manifested macroscopically as the tear strength reaches the maximum value first, and the material is more easily destroyed under the tearing effect. This embodiment found through experiments that when the hydrophobic fumed silica accounts for 11-19% of the total mass of the hydroxy silicone resin, the mechanical strength of the obtained polymer insulating material becomes stronger as the proportion of hydrophobic fumed silica increases.
[0038] In some embodiments, a method for preparing a polymer insulation material for a 110 kV overhead bare conductor is also provided, such as Figure 1 As shown, it includes the steps of:
[0039] S10, adding FD20 hydroxy silicone resin, FD80 hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microspheres and magnesium hydroxide into a disperser in sequence, stirring and dispersing, passing cooling water, evacuating to -0.09 to -0.1 MPa, and continuing to disperse for 30-60 minutes to obtain a first mixed material;
[0040] S20, transferring the first mixture to a three-roll mill for grinding, then transferring the first mixture to a disperser, adding methyltrimethoxysilane and vinyltrimethoxysilane, adding cooling water for dispersion, then adding calcium carbonate and hydrophobic fumed silica, dispersing and mixing for 10-30 minutes, evacuating to a vacuum degree of -0.09 to -0.1 MPa, maintaining for 30-50 minutes, stopping stirring and dispersing, releasing the vacuum, and obtaining a second mixture;
[0041] S30, adding platinum catalyst, aminopropyl triethoxysilane and black slurry to the second mixture, stirring and dispersing, and finally adjusting the viscosity by adding hydroxy silicone resin with a viscosity of 350 cs to prepare a polymer insulation material for 110 kV overhead bare conductors.
[0042] Specifically, in order to ensure uniform mixing of the materials, the speed of the dispersant is 1800-2500r / min. The preparation method provided in this embodiment is simple and easy to operate. The obtained polymer insulating material is a single-component high-viscosity room-temperature curing liquid insulating material, with a solid content greater than 99.99% and a density of 1.2-1.3g / cm 3 , by using a special coating robot, the polymer insulation material is coated on the 110kV overhead bare wire, which can insulate the surface of the bare wire and tightly wrap the overhead bare wire to prevent leakage accidents. The polymer insulation material provided by the present invention has been tested many times, and its AC breakdown voltage can reach 130kV / 6mm. Due to the silicone system, its service life reaches more than 15 years. The polymer insulation material provided by the present invention is cured at room temperature, the surface curing time is 30min, and the complete curing time is 24h. It can be energized and operated when coated on the overhead bare wire without affecting its load-bearing capacity; the polymer insulation material of the present invention has excellent mechanical properties, its tensile strength reaches 10.8MPa, and its elongation at break reaches 680%. After aging for 1008h, the change rate of tensile strength is only -5.18%, and the change rate of elongation at break is only -12.67, showing better weather resistance and mechanical strength.
[0043] The present invention will be further explained below by means of specific embodiments:
[0044] Example 1
[0045] A polymer insulating material for 110kV overhead bare conductors comprises, by weight: 52.5 parts of hydroxy silicone resin of model FD20, 8.3 parts of hydroxy silicone resin of model TH-3051, 14 parts of fluorosilicone resin, 50 parts of tetrafluoroethylene, 8 parts of hollow glass microspheres, 0.8 parts of magnesium hydroxide, 0.22 parts of methyltrimethoxysilane, 4.8 parts of vinyltrimethoxysilane, 4 parts of calcium carbonate, 10 parts of hydrophobic fumed silica, 2 parts of platinum catalyst, 1.3 parts of aminopropyltriethoxysilane, 0.22 parts of black paste, and 1.0 parts of hydroxy silicone resin with a viscosity of 350cs.
[0046] The preparation of the polymer insulating material in this embodiment includes the following steps:
[0047] 1. Add FD20 hydroxy silicone resin, FD80 hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microspheres and magnesium hydroxide into a disperser in sequence, stir and disperse them, pass cooling water, evacuate to -0.09Mpa, continue to disperse for 40 minutes, and obtain the first mixture. The speed of the disperser is 2000r / min;
[0048] 2. After the first mixture is transferred to a three-roll mill for grinding, the first mixture is transferred to a disperser, methyltrimethoxysilane and vinyltrimethoxysilane are added, cooling water is added for dispersion, and then calcium carbonate and hydrophobic fumed silica are added. The mixture is dispersed and mixed for 20 minutes, and the vacuum is evacuated to a vacuum degree of -0.09 MPa, maintained for 40 minutes, and stirring and dispersing is stopped. The vacuum is released to obtain a second mixture. The speed of the disperser is 2000 r / min;
[0049] 3. Add platinum catalyst, aminopropyl triethoxysilane and black slurry to the second mixture, stir and disperse, and finally adjust the viscosity by adding hydroxy silicone resin with a viscosity of 350 cs to prepare a polymer insulation material for 110 kV overhead bare conductors.
[0050] Example 2
[0051] A polymer insulating material for 110kV overhead bare conductors comprises, by weight: 52 parts of hydroxy silicone resin of model FD20, 8 parts of hydroxy silicone resin of model TH-3051, 12 parts of fluorosilicone resin, 48 parts of tetrafluoroethylene, 5 parts of hollow glass microspheres, 0.5 parts of magnesium hydroxide, 0.2 parts of methyltrimethoxysilane, 4.5 parts of vinyltrimethoxysilane, 2 parts of calcium carbonate, 7 parts of hydrophobic fumed white carbon black, 1.5 parts of platinum catalyst, 1 part of aminopropyltriethoxysilane, 0.2 parts of black paste, and 0.5 parts of hydroxy silicone resin with a viscosity of 350cs.
[0052] The preparation of the polymer insulating material in this embodiment includes the following steps:
[0053] 1. Add FD20 hydroxy silicone resin, FD80 hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microspheres and magnesium hydroxide into a disperser in sequence, stir and disperse them, pass cooling water, evacuate to -0.1Mpa, continue to disperse for 30 minutes, and obtain the first mixture. The speed of the disperser is 1800r / min;
[0054] 2. After the first mixture is transferred to a three-roll mill for grinding, the first mixture is transferred to a disperser, methyltrimethoxysilane and vinyltrimethoxysilane are added, cooling water is added for dispersion, and then calcium carbonate and hydrophobic fumed silica are added. The mixture is dispersed and mixed for 10 minutes, and the vacuum is evacuated to a vacuum degree of -0.09 MPa, maintained for 50 minutes, and stirring and dispersing is stopped. The vacuum is released to obtain a second mixture. The speed of the disperser is 1800 r / min;
[0055] 3. Add platinum catalyst, aminopropyl triethoxysilane and black slurry to the second mixture, stir and disperse, and finally adjust the viscosity by adding hydroxy silicone resin with a viscosity of 350 cs to prepare a polymer insulation material for 110 kV overhead bare conductors.
[0056] Example 3
[0057] A polymer insulating material for 110kV overhead bare conductors comprises, by weight: 53 parts of hydroxy silicone resin of model FD20, 8.5 parts of hydroxy silicone resin of model TH-3051, 16 parts of fluorosilicone resin, 55 parts of tetrafluoroethylene, 10 parts of hollow glass microspheres, 1 part of magnesium hydroxide, 0.25 parts of methyltrimethoxysilane, 5 parts of vinyltrimethoxysilane, 2-5 parts of calcium carbonate, 11 parts of hydrophobic fumed white carbon black, 2.5 parts of platinum catalyst, 1.5 parts of aminopropyltriethoxysilane, 0.25 parts of black paste, and 1.5 parts of hydroxy silicone resin with a viscosity of 350cs.
[0058] The preparation of the polymer insulating material in this embodiment includes the following steps:
[0059] 1. Add FD20 hydroxy silicone resin, FD80 hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microspheres and magnesium hydroxide into a disperser in sequence, stir and disperse them, pass cooling water, evacuate to -0.1Mpa, continue to disperse for 60 minutes, and obtain the first mixture. The speed of the disperser is 2500r / min;
[0060] 2. After the first mixture is transferred to a three-roll mill for grinding, the first mixture is transferred to a disperser, methyltrimethoxysilane and vinyltrimethoxysilane are added, cooling water is added for dispersion, and then calcium carbonate and hydrophobic fumed silica are added. The mixture is dispersed and mixed for 30 minutes, and the vacuum is evacuated to a vacuum degree of -0.09 MPa, maintained for 30 minutes, and stirring and dispersing is stopped. The vacuum is released to obtain a second mixture. The speed of the disperser is 2500 r / min;
[0061] 3. Add platinum catalyst, aminopropyl triethoxysilane and black slurry to the second mixture, stir and disperse, and finally adjust the viscosity by adding hydroxy silicone resin with a viscosity of 350 cs to prepare a polymer insulation material for 110 kV overhead bare conductors.
[0062] Test Case
[0063] like Figure 2 As shown, on a 110kV overhead bare conductor (LGJ-240 / 20), a coating machine was used to coat 8 meters of the polymer insulation material prepared in Example 1. After complete curing, the coated cable was cut and sent to a third party (Guangzhou High-speed Railway Measurement and Monitoring Co., Ltd.) for testing. To ensure the accuracy of the test, the 110kV insulation coating material met the following conditions during the performance test:
[0064] The coating test was carried out in good weather, sunny, wind force 3.
[0065] Humidity: Daily relative humidity 85%.
[0066] Working environment temperature: +30℃.
[0067] Application: 110kV overhead bare conductor (LGJ-240 / 20).
[0068] Test method: Conduct live coating operation through the matching coating device.
[0069] This embodiment firstly performs a power frequency breakdown voltage test. Figure 3 Therefore, the insulation coating thickness of the sample is 6.3mm. When the test voltage reaches 80kV, creepage begins on the surface of the sample insulation layer, which is a flashover phenomenon. When the voltage reaches 130kV, the insulation layer breaks down.
[0070] Then the physical and mechanical properties of the prepared overhead insulated wire were tested, and the test results are shown in Table 1.
[0071] Table 1 Mechanical properties test results
[0072]
[0073]
[0074] The above test data is obtained according to the following standards:
[0075] 1. GB / T1033.1-2008 "Determination of density of non-foamed plastics Part 1: Immersion method, liquid pycnometer method and titration method";
[0076] 2. GB / T 531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber - Part 1: Shore durometer method (Shore hardness)";
[0077] 3. GB / T 14049-2008 "Overhead insulated cables with rated voltage of 10kV";
[0078] 4. GB / T 9286-1998 Specification test for paint and varnish films;
[0079] 5. GB / T 15022.2-2017 “Resin-based active composites for electrical insulation Part 2: Test methods”.
[0080] It can be seen from the test results in Table 1 that the samples submitted for inspection of the present invention are tested in accordance with GB / T1033.1-2008, GB / T531.1-2008, GB / T 14049-2008, GB / T 9286-1998 and GB / T 15022.2-2017 standards, and all items meet the specified requirements. The polymer insulating material prepared in Example 1 is a single-component high-viscosity room-temperature curing liquid insulating material, with a solid content greater than 99.99% and a density of 1.2-1.3 g / cm 3 , by using a special coating robot, the polymer insulation material is coated on the 110kV overhead bare wire, which can insulate the surface of the bare wire and tightly wrap the overhead bare wire to prevent leakage accidents. The polymer insulation material provided by the present invention has been tested many times, and its AC breakdown voltage can reach 130kV / 6mm. Due to the silicone system, its service life reaches more than 15 years. The polymer insulation material provided by the present invention is cured at room temperature, the surface curing time is 30min, and the complete curing time is 24h. It can be energized and operated when coated on the overhead bare wire without affecting its load-bearing capacity; the polymer insulation material of the present invention has excellent mechanical properties, its tensile strength reaches 10.8MPa, and its elongation at break reaches 680%. After aging for 1008h, the change rate of tensile strength is only -5.18%, and the change rate of elongation at break is only -12.67, showing better weather resistance and mechanical strength.
[0081] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A polymer insulating material for 110kV overhead bare conductor, characterized in that: The invention comprises, by weight: 52-53 parts of hydroxy silicone resin of model FD20, 8-8.5 parts of hydroxy silicone resin of model TH-3051, 12-16 parts of fluorosilicone resin, 48-55 parts of tetrafluoroethylene, 5-10 parts of hollow glass microspheres, 0.5-1 parts of magnesium hydroxide, 0.2-0.25 parts of methyltrimethoxysilane, 4.5-5 parts of vinyltrimethoxysilane, 2-5 parts of calcium carbonate, 7-11 parts of hydrophobic fumed silica, 1.5-2.5 parts of platinum catalyst, 1-1.5 parts of aminopropyltriethoxysilane, 0.2-0.25 parts of black paste, and 0.5-1.5 parts of hydroxy silicone resin with a viscosity of 350cs.
2. The polymer insulating material for 110kV overhead bare conductor according to claim 1, characterized in that: The hollow glass microspheres are spherical powdered materials with a hollow structure, with hard glass on the outside and inert gas on the inside. The particle size is 5-100 microns and the density is 0.3-0.8 g / ml.
3. The polymer insulating material for 110kV overhead bare conductor according to claim 2, characterized in that: The hollow glass microspheres include, by mass percentage, 55-65% SiO2, 26-35% Al2O3, 0.2-1% Fe2O3, 0.5-4% Na2O, 0.5-4% K2O, 0.2-0.6% CaO, 1-2% MgO, and 0.5-2% TiO2.
4. The polymer insulating material for 110kV overhead bare conductor according to claim 1, characterized in that: The hydrophobic fumed silica in the polymer insulating material accounts for 11-19% of the total mass of the hydroxy silicone resin.
5. The polymer insulating material for 110kV overhead bare conductor according to claim 1, characterized in that: The specific surface area of the hydrophobic fumed silica is 150-400m 2 / g, silicon dioxide content ≥99.8%.
6. The polymer insulating material for 110kV overhead bare conductor according to claim 1, characterized in that: The density of the methyltrimethoxysilane is 0.955 g / cm 3 , boiling point is 102-104°C, refractive index is 1.371; density of the vinyl trimethoxysilane is 0.9±0.1g / cm 3 , boiling point is 123℃, and refractive index is 1.3920.
7. The polymer insulating material for 110kV overhead bare conductor according to claim 1, characterized in that: The model of the platinum catalyst is CAT-PL-56, and the platinum ion concentration thereof is 50000 ppm.
8. The polymer insulating material for 110kV overhead bare conductor according to claim 1, characterized in that: The model of the fluorosilicone resin is LS8722, the fluorine content thereof is 40%, and the viscosity is 100000 cs.
9. A method for preparing a polymer insulating material as claimed in any one of claims 1 to 8, characterized in that: Includes steps: Add FD20 hydroxy silicone resin, FD80 hydroxy silicone resin, fluorosilicone resin, tetrafluoroethylene, hollow glass microspheres and magnesium hydroxide into a disperser in sequence, stir and disperse them, pass cooling water, evacuate to -0.09 to -0.1 MPa, and continue to disperse for 30-60 minutes to obtain a first mixed material; The first mixed material is transferred to a three-roll mill for grinding, and then the first mixed material is transferred to a disperser, methyltrimethoxysilane and vinyltrimethoxysilane are added, cooling water is added for dispersion, and then calcium carbonate and hydrophobic fumed silica are added, dispersed and mixed for 10-30 minutes, and vacuumed to a vacuum degree of -0.09 to -0.1Mpa, maintained for 30-50 minutes, and stirring and dispersing is stopped, and the vacuum is released to obtain a second mixed material; Platinum catalyst, aminopropyl triethoxysilane and black slurry were added to the second mixture, and after stirring and dispersing, the viscosity was adjusted by adding hydroxy silicone resin with a viscosity of 350 cs to prepare a polymer insulation material for 110 kV overhead bare conductors.
10. The method for preparing a polymer insulating material according to claim 9, characterized in that: The rotating speed of the disperser is 1800-2500 r / min.